An Examination of the Influence of Non-governmental Organizations on the Welfare of the Elderly in Kauga Village Mukono Central Division - Godfrey Mutebi (Uganda Christian University, 2024)
The study examines the influence of NGOs on the welfare of the elderly in Mukono Municipality, kauga village. A mixed survey methods approach was used, involving surveys and interviews with the elderly participants and NGOs representatives. Results show significant improvement in social, health care services, economic and as well as reduced dependence on the NGO assistance this ahs been proven achieveable through the support and interventions made by the various NGOs towards the welfare of the elderly.
DISSERTATION